Elevated Salivary Inflammatory Biomarkers are Associated with SARS-CoV-2 Infection Severity - Hanadi Abdullah Alwafi; Soad Shaker Ali; Sunil Babu Kotha; Layla Waleed Abuljadayel; Maha Ibrahim; Ibrahim Rashad Noor Elahi; Hebah Abdullah Alwafi; Mohammed S. Almuhayawi; Matthew D. Finkelman; Nagla A. El-Shitany (Canadian Journal of Infectious Diseases and Medical Microbiology)
High levels of inflammatory cytokines in serum have been reported in patients with severe SARS-CoV-2 infection. There is growing interest in recognizing the role of inflammatory biomarkers in saliva in diagnosing systemic diseases. This study assumed that estimating biomarkers in saliva samples from patients infected with SARS-CoV-2 would distinguish between mild and severe cases. Saliva was collected from 142 controls and 158 SARS-CoV-2 patients (mild 72 and severe 86) to measure interleukin-6 (IL-6), C-reactive protein (CRP), and C-X-C motif chemokine ligand-10 (CXCL-10). IL-6 and CXCL-10 were significantly increased in patients with mild and severe SARS-CoV-2 infections. CRP was significantly increased only in severe SARS-CoV-2 cases. All biomarkers were significantly higher in severe cases than in mild cases (p<0.001). Among patients with SARS-CoV-2 infection, men showed significantly higher CRP and CXCL-10 levels than females (p<0.01 and 0.05, respectively). In addition, elderly patients (40–80 years) had significantly higher IL-6, CRP, and CXCL-10 (p<0.001). Patients with diabetes and hypertension showed elevated IL-6, CRP, and CXCL-10 (p<0.001). There was a significant positive correlation between IL-6, CRP, CXCL-10, and between age, IL-6, CRP, and CXCL-10. Saliva may have a future value in measuring the inflammatory biomarkers associated with the severity of SARS-CoV2 infection and therapeutic monitoring.